IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS TEACHER CENTER LEARNING (TCL) DAN STUDENT CENTER LEARNING (SCL) PADA STMIK ANTAR BANGSA - Tarmizi, Tarmizi; Mansur, Jam'an Nurchotib (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2024)
The Islamic Religious Education (PAI) course is a compulsory course that must be followed by students, as well as PAI subjects at the elementary, junior high and high school levels. In the learning process, an educator who is effective in PAI courses must have the ability to transfer knowledge and values, this requires innovation in learning methods so that teaching materials and learning objectives can be well received. The learning strategies of Teacher Centered Learning (TCL) and Student Centered Learning (SCL) can be an educator's choice in transferring knowledge. This research was conducted at STMIK Antar Bangsa using a quantitative research method with a predetermined population and sample, or the technique used was non-random sampling, while the data analysis used the Statistical Package for the Social Sciences (SPSS) application. Based on the results of data analysis from the questionnaire, it was found that the application of the SCL learning approach was more dominant than TCL, this was evidenced by quite high results in SCL activities, such as cooperation between students, feedback from lecturers regarding the tasks given, and lecturers involving students in making decisions about learning materials and learning methods to be carried out. The TCL approach is also still used by PAI lecturers, in the process of delivering material still uses the careful method as well as in doing individual assignments, students tend to do it themselves.